AMAR MA‘RUF NAHī MUNKAR: SEBUAH KAJIAN ONTOLOGIS - Badarussyamsi Badarussyamsi; Mohammad Ridwan; Nur Aiman (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
This article examines ontologically the term